Notes on an enigmatic Bornean megophryid, Leptolalax dringi Dubois, 1987 (Amphibia: Anura) - Matsui, Masafumi; Dehling, J. Maximilian (Zootaxa, 2012)
The original description of the Bornean megophryid Leptolalax dringi was not sufficient to differentiate the species fromits Bornean congeners. The species was later re-described but the redescription included characters from both type spec-imens and Leptolalax from other sites, including undescribed species. Analyses of the advertisement call of specimensassigned to L. dringi have been published but call descriptions differ markedly from each other. Moreover, published pic-tures of L. dringi are dubious in identification. Thus, the identity of L. dringi is enigmatic, hindering taxonomic work onBornean Leptolalax. We herein provide detailed descriptions of the type series as well as recently obtained topotypic spec-imens. We also present the results of an analysis of the advertisement call of a male paratype. These data will facilitate future taxonomic work on Bornean Leptolalax.